The Iconic Word: The Theological and Rhetorical Sources of a New Ut Pictura Poesis - Anne-Marie Miller-Blaise (Sillages Critiques)
This article questions the Renaissance, humanist understanding of the Horatian adage, Ut Pictura Poesis, and endeavors to elucidate the specific ways in which a lyric poem can be considered as an object to be looked at. The early modern poetic production of Sir Philip Sidney (1554-1586) and of his distant relation George Herbert (1593-1633) testifies to a crisis of the mimetic and ekphrastic powers of poetry. Written in a period following the iconoclast English Reformation and at a time when the humanist faith in the imitative powers of the artist was starting to splinter, their poetry substitutes a new form of visual materiality for the failing art of mimesis. Interestingly, it may help to account for the sense of awe and reverence we still experience when we behold a poem inscribed within the white “temple” of the page.